2011
DOI: 10.1016/j.metabol.2010.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of metabolic abnormalities in adolescents and young adults with HIV-infection acquired perinatally or in early childhood

Abstract: Objective Metabolic complications of HIV pose challenges for health maintenance among young adults who acquired HIV in early childhood. Materials/Methods Between 7/2004–7/2009 we evaluated 47 HIV-infected subjects who acquired HIV in early life. Participants completed glucose tolerance testing, insulin, lipid, urine albumin and creatinine determinations and DXA scans. Longitudinal data were available for 39 subjects; duration of follow-up was 26.4±16.8 months. Results At baseline, participants were 17.1±3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 40 publications
4
42
3
Order By: Relevance
“…A common occurrence during the perinatal period is exposure to infection, which activates the host immune response. Early life immune activation is known to impact normal development in both animals and humans resulting in long-term metabolic (Dimock et al, 2011;Walker et al, 2006), immune (Galic et al, 2009;Hodgson et al, 2001;Martinez et al, 1998;Walker et al, 2010), neuroendocrine (Matthews, 2002;Shanks et al, 2000) and behavioural (Meyer et al, 2006;Walker et al, 2009b) alterations. Sexual dimorphism in response to a neonatal immune challenge has also been recently shown to predict differences in adult immune and behavioural responses to inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…A common occurrence during the perinatal period is exposure to infection, which activates the host immune response. Early life immune activation is known to impact normal development in both animals and humans resulting in long-term metabolic (Dimock et al, 2011;Walker et al, 2006), immune (Galic et al, 2009;Hodgson et al, 2001;Martinez et al, 1998;Walker et al, 2010), neuroendocrine (Matthews, 2002;Shanks et al, 2000) and behavioural (Meyer et al, 2006;Walker et al, 2009b) alterations. Sexual dimorphism in response to a neonatal immune challenge has also been recently shown to predict differences in adult immune and behavioural responses to inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…Dimock [18] from Bethesda in US reported a prevalence of 15%. The differences between the results from studies conducted in Congo, Tanzania and our data could be the result of the small size of the sample used for our study.…”
Section: Discussionmentioning
confidence: 99%
“…Microalbuminuria, which is a marker for vascular disease or injury, was present in 15% of participants and was inversely correlated with CD4% (P=0.001). While the study lacked a control sample, these data indicate that long-term exposure to ART may substantially increase metabolic risk for adolescents and young adults facing lifelong HIV infection and therapy [20].…”
Section: Lipids/inflammation/biomarkersmentioning
confidence: 92%
“…Dimock et al [20] analyzed metabolic parameters in 47 HIV-infected adolescents and young adults (mean age 17 years) who acquired HIV in early life. This study found that 15% of their population had impaired glucose tolerance, 33% had insulin resistance, 52% had elevated triglycerides, 36% had low HDL, 18% had high LDL, and 25% had high levels of total cholesterol.…”
Section: Lipids/inflammation/biomarkersmentioning
confidence: 99%